Inflammation and end-organ damage with obesity and gender - Bloor, Ian David (2012)
Latest epidemiological data suggests that 1.5 billion adults worldwide are obese or overweight. Excess weight and adipocyte hypertrophy have long been associated with contributing to low-grade systemic inflammation through elevated adipokine secretion. These increased endocrine signals further augment the metabolic dysfunction related to the presence of obesity. A chronic exposure to obesity mediated inflammation is also suggested to be responsible for progression of renal pathology and eventual end-stage organ failure. In human clinical statistics, these factors indicate a gender disparity, as males demonstrate much faster progression rates of obesity-linked renal disease than females. Therefore, the aim of this thesis was to investigate the role of gender in obesity mediated inflammation in the development of renal disease using a large animal model i.e. sheep.